BODY IMAGE, FEAR OF REJECTION AND SELF-ESTEEM AMONG PERSONS WITH CLEFT LIP AND PALATE - Hajra Imran; Dr. Saleem Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
The objective of the present was investigated the relationship between body image, fear of rejection and self-esteem among persons with cleft lip and palate. Once the review of the literature following hypotheses were formulated 1). There would be significant relationship between Body image, fear of rejection and self-esteem among persons with cleft lip and palate 2). Body image would predict fear of rejection and self-esteem among persons with cleft lip and palate 3) Gender would exhibit significant differences on Body image, fear of rejection and self-esteem among persons with cleft lip and palate. Total 75 persons with cleft lip and palate (35 male and 40 female) were selected through snow ball sampling method. In order to calculate results t-test, person correlation and regression analysis and independent sample t-test would use. Findings of the present study have shown that 1st 2nd hypotheses have approved P<.05 while 3rd hypothesis was rejected P>.05. At the end of thesis implication, suggestion of the present study and recommendation for the future studies was discussed in details.